The sandwich swap - Rania, Queen, consort of Abdullah II, King of Jordan, 1970- (Disney-Hyperion Books, 2010)
Best friends Lily and Salma disagree over their preferred foods, but after trading sandwiches to see how they taste, the girls change their minds.